Temperature dependence of femtosecond photoacoustic process in high-precision characterization for metal nanofilms - Zhongyu Wang; Jing Min; Yong Sun; Xuesong Wang; Xiuguo Chen; Zirong Tang; Shiyuan Liu (Photoacoustics)
Femtosecond photoacoustic detection is a powerful all-optical technique for characterizing metal nanofilms. However, the lack of accurate descriptions of the temperature-dependent optical properties of metal nanofilms during ultrafast thermal processes hinders the deep understanding of this dynamic behavior, leading to compromised measurement accuracy. To address this, we developed Critical Point Models (CPMs) for copper and AlCu nanofilms to describe their dynamic optical properties during photoacoustic testing. By integrating dynamic behavior into ultrafast laser-matter interaction and acousto-optic processes, we explored the temperature effects throughout testing. Numerical simulations were performed to analyze the temperature, stress, and surface reflectivity distributions of the nanofilms. Compared to experimental results, our dynamic models significantly improved prediction accuracy for both copper and AlCu nanofilms. This highlights the importance of temperature dependence in femtosecond photoacoustic testing and validates our model's capability to capture the behavior of metal nanofilms under ultrafast laser irradiation.